Negative Affect and Vasomotor Symptoms in the Study of Women's Health Across the Nation (SWAN) Daily Hormone Study - Gibson, Carolyn J. (2011)
OBJECTIVE: Vasomotor symptoms (VMS) are common during the menopausal transition. Negative affect is consistently associated with self-reported VMS, but interpretation of this relationship is limited by infrequent measurement and retrospective recall of VMS. Using prospective data from daily diaries, we examined the daily association between negative affect and reported VMS, as well as temporal associations between negative affect and next day VMS, and VMS and next day negative affect. METHODS: Data were derived from the third wave of the Daily Hormone Study (DHS) (n=625). DHS is a substudy of the Study of Women's Health Across the Nation (SWAN), a multi-site community-based prospective cohort study of the menopausal transition. Participants reported VMS and affect in daily diaries for 12–50 days. Multilevel mixed models were used to determine the associations between reported VMS and negative affect, adjusted by antidepressant use, age, education, menopausal status, self-reported health, and race/ethnicity drawn from annual SWAN visits. RESULTS: VMS were reported by 327 women (52.3%). Negative affect was positively associated with VMS (OR 1.76, 95% CI 1.43–2.17, p<.001) in cross-sectional analyses. Negative affect, adjusted by same day VMS, was not predictive of next day VMS (OR 1.11, 95% CI .85–1.35, p=.55), whereas VMS, adjusted by same day negative affect, was predictive of negative affect the next day (OR 1.27, 95% CI 1.03–1.58, p=.01). CONCLUSIONS: Negative affect was more likely to be reported on the same day and the day after VMS. Potential mechanisms underlying this relationship include negative cognitive appraisal, sleep disruption, and unmeasured third factors.